PERAN JAKSA PENGACARA NEGARA DALAM MELAKUKAN NEGOSIASI TERHADAP SENGKETA PERDATA DI KEJAKSAAN NEGERI BULELENG - Andreina Avelia Novin Br. Simatupang; Si Ngurah Ardhya; Made Sugi Hartono (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2025)
This study aims to analyze the role of the State Attorney (JPN) in negotiating civil dispute settlements through non-litigation mechanisms at the Buleleng District Prosecutor’s Office. The research focuses on legal assistance requested by Pegadaian and BPJS Kesehatan due to payment defaults by debtors. Using an empirical legal approach, data were collected through observations, interviews, and document studies. The findings reveal that JPN has the authority to represent the state or government in civil cases based on a Special Power of Attorney (SKK). In practice, the negotiations conducted by JPN have produced mutually beneficial outcomes; however, their implementation has not been fully optimal as some business entities fail to comply with negotiated agreements. The study recommends enhancing JPN's preventive and persuasive roles to improve the effectiveness of non-litigation dispute resolution and to reinforce the function of legal mediation in ensuring justice and legal certainty for all parties involved.